The Case for Collaboration to Foster Global Ocean Literacy - Marrero, Meghan E.; Payne, Diana L.; Breidahl, Harry (Frontiers in Marine Science, 2019)
The global ocean literacy movement began with a collaborative effort of like-minded individuals. This commentary highlights the role of marine education networks in the work of global ocean literacy, and discusses the importance of collaboration and action to promote a sustainable ocean future.